Functional Assessment of Rural Counties Under the Production–Living–Ecological Framework: Evidence from Guangdong, China - Hongping Lian; Yuedong Zhang; Xuezhen Xiong; Wenjing Han (Land)
This study focuses on 67 counties in Guangdong Province, China, and investigates the spatial distribution patterns, regional differentiation characteristics, and functional zoning of rural areas based on the “Production–Living–Ecological” (PLE) functional synergy theoretical framework. Multiple quantitative methods, including the entropy method, spatial concentration degree, and functional identification, were employed. Key findings include: (1) Rural functions in Guangdong exhibit significant heterogeneous evolution. Production functions have generally weakened, showing a spatial pattern of “consolidation in the south and decline in the north”. Ecological functions demonstrate a U-shaped recovery trend, with high-value areas concentrating around the Pearl River Delta urban agglomeration, indicating effective ecological protection policies. Living functions continue to decline due to population mobility and imbalanced public services. (2) Structural transformation of rural function types occurred: Weakly integrated counties decreased (2010–2019), dual function type counties (production–ecological and living–ecological) significantly increased, and ecology-dominant counties predominated, highlighting ecological polarization under policy interventions. (3) Functional evolution is driven by terrain gradients, policy regulation, and industrial relocation. The research provides empirical evidence for optimizing territorial spatial governance and coordinating urban–rural development. Recommendations include promoting dynamic PLE balance through high-standard farmland construction, ecological industrialization cultivation, and cross-regional compensation mechanisms to facilitate rural revitalization and sustainable development.